ASSISTED INDIVIDUALIZATION (TAI) BERBANTU MEDIA KARTU MASALAH UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS X DI SMA NEGERI 2 SINGINGI KABUPATEN KUANTAN SINGINGI - Resti Resti Komalasari; Sopiatun Nahwiyah; Zulhaini Zulhaini (Universitas Islam Kuantan Singingi, 2023)
As for the backgroud of this research is the low learning achievement of grade X students in religious education subjects. Grade X students’ grades are still relatively low, many of them do not reach the minimum completeness criteria (KKM), there are students who are less active in asking questions, and the lack of enthusiasm of students in participating in learning. This is a problem that the author got based on observations with teachers of islamic religious education subjects and character. The purpose of this research is to improve student achievement class X at SMA Negeri 2 Singingi kabupaten Kuantan Singingi. By using data collection techniques through interview observations as well as data processing using percentage graphs. The model used in this research is model Team Assisted Individualization (TAI) which is one of the cooperative learning models that is carried out by placing students in small groups heterogeneous. Team Assisted Individualization (TAI) is learning model that can improve student achievement, improve students’ problem solving skills and train students to work together in groups. From research results application of learning models Team Assisted Individualization (TAI) can improve student achievement class X on subjects PAI-BP at SMA Negeri 2 Singingi Kabupaten Kuantan Singingi. This is evident from the results of the pre-cycle student achievement 35,71%, cycle I becomes 60,71 %, and cycle II increased to 8,71%.